MM. Dr. P. V. Kane commemoration monograph - Kāṇe, Pāṇḍuraṅga Vāmana, b. 1880; Gajendragadkar, S. N. (University of Bombay, 1974)
Commemoration volume on Pandurang Vaman Kane, 1880-1972, Sans krit scholar.